Erectile Dysfunction and Ejaculatory Dysfunction in Covid-19 Recovered Patient: Temporary or Persistent? - Hadibrata, Exsa; Sutyarso, Sutyarso; Busman, Hendri; Sumardi, Sumardi (Urology Journal, 2025)
Purpose: Examine the prevalence of erectile dysfunction and ejaculatory dysfunction among COVID-19 recovered patients and whether this condition improved over time. The retrospective study of 50 male patients who have recovered from COVID-19 infection previously hospitalized in dr. H Abdul Moeloek General Hospital between March 2020 – March 2021. Materials and Methods: All of these patients were evaluated in terms of erectile and ejaculation function via phone interview. The International Index of Erectile Function 5 (IIEF-5) and Male sexual health questionnaire ejaculatory dysfunction (MHSQ-EJD) were used to assess the erectile function and ejaculatory dysfunction. Statistical analysis was performed to evaluate whether there was a difference between IIEF-5 & MHSQ-EJD scores within 6 months, 6 to 12 months, and >24 months after COVID-19 infection. Results: The prevalence of ED was 70% and EJD was 2 % during 0-6 months after COVID-19 infection. Mean age and BMI were 50.4 ± 8.5 years and 23.6 ± 1.6 kg/m2 respectively. There are 26 patients (52%) had an educational background lower than bachelor’s degree and 24 patients (48%) had an educational background of bachelor’s degree or higher. It was reported that 4 patients (8%) had Diabetes Mellitus and 12 patients (24%) had Hypertension. Most were active smokers (74%) and 2 patients (4%) had reported as active alcohol drinkers. There was a statistically significant IIEF-5 scores difference between three periods of time (p <0,001). Conclusion: The prevalence of Erectile Dysfunction was high in COVID-19 recovered patients. There was a temporary erectile dysfunction and ejaculatory dysfunction among COVID-19 patients.